TRANSFORMATION OF MARGA GOVERNANCE IN SOUTH SUMATRA: A COMPARATIVE ANALYSIS OF THE DUTCH COLONIAL ERA AND THE REPUBLIC OF INDONESIA, 1825-1983 - Wijaya, Tomy; Alauwiyah, Fatimah (Universitas Padjadjaran, 2025)
This research examines the significant transformation of the clan governance system in South Sumatra under two distinct power regimes: the Dutch colonial period and the Republic of Indonesia (1825–1983). Despite the clan being a well-established customary institution in local governance, limited research has systematically analyzed the dynamics of its administrative transformation across the two periods, particularly regarding contemporary state pressures and institutional reconfiguration. This research aims to address this gap by examining the processes of co-optation, adaptation, and de-institutionalization of the clan system by the state, employing a historical approach within the theoretical frameworks of historical institutionalism and institutional isomorphism. The employed methods consist of heuristics, source criticism, interpretation, and historiography. The findings indicate that during the colonial era, the clan system was not eradicated but rather institutionalized within the colonial governance framework via an indirect administration approach. During the era of the Republic of Indonesia, this system was integrated into the administrative village framework through a centralization policy; however, the values and social practices of the clan persisted at the local level. This study concludes that institutional change is intricate and results in a hybrid configuration that exemplifies the coexistence of formal state systems and local customary systems.